Culturas urbanas e investigación en Quito. - Ogaz Buitrón, Sebastián Ernesto (2017)
The present work invites us to know a little more about urban cultures in our current context as a way of understanding and approaching a reality; Proposes a revision on the different forms of approach from the academic and institutional environment that have been generated on the diversity within the framework of the urban cultures that converge with a universe of senses, practices that are heterogeneous in their cultural diversity. In this way, the present academic article proposes in a first part a review on the forms of approach and understanding of the social phenomenon of emerging urban cultures in our local reality, and the different actors and organizations that have been involved in the Task of thinking about, for and from the cultural diversity in our local environment. In the second part of the paper, we go into various areas of research at the local level to clarify and understand the main concepts, debates, problems and contradictions that the actors involved in research in urban cultures pose, culminating in a balance with the main contributions that Both the actors and the debates exposed give us in relation to the studies on urban cultures.